Застосування трирівневої концепції мерчандайзингу для формування купівельної лояльності - Парфентенко, Ірина Анатоліївна (Українська державна академія залізничного транспорту, 2018)
Проаналізовано існуючі підходи до визначення поняття "купівельна лояльність". Визначено та обґрунтовано необхідність застосування трирівневої концепції мерчандайзингу, його інструментів і правил в процесі формування купівельної лояльності. Удосконалено понятійно-категоріальний апарат з проблематики дослідження, зокрема, визначення цілей мерчандайзингу в роздрібній торгівлі шляхом встановлення логічного взаємозв'язку між базовими поняттями "поведінка споживачів", "процес прийняття споживачем рішення про покупку", "мерчандайзинг", "купівельна лояльність".

The article analyzes the existing approaches to the definition of "consumer loyalty". The necessity of application of the three-level concept of merchandising, its tools and rules in the process of formation of consumer loyalty has been determined and substantiated. The key factors of the success of the market activity of the enterprise and the principles of building long-term relations with clients are investigated. The main tools of formation of consumer loyalty are outlined and their scope of application is outlined. The three-level concept of merchandising, which involves the use of visual elements for the creation of a suitable favorable atmosphere on the basis of psychophysiological behavioral laws, is proposed in order to form a long-term customer loyalty and construct an emotional attachment to the brand. The conceptual-categorical apparatus on research issues was improved, in particular, the definition of the objectives of merchandising in retail trade by establishing a logical relationship between the basic concepts of "consumer behavior", "the process of consumer acceptance of a purchase decision", "merchandising", "consumer loyalty".
Application of the third concept of mirchandaising for forming buying loyality
Keywords: купівельна лояльність; трирівнева концепція мерчандайзингу; завдання мерчандайзингу; бренд; мерчандайзинг; three-level concept of merchandising; task of merchandising; consumer loyalty; brand